2004
DOI: 10.1007/s00204-004-0557-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the glutathione system of lung cell lines after treatment with hydrocortisone

Abstract: Administration of anti-inflammatory glucocorticoids is a drug option in the therapy of acute respiratory distress syndrome (ARDS), according to present pathophysiological concepts. Surprisingly, glucocorticoids failed to show beneficial effects. This failure is not understood. In this investigation changes in the glutathione system due to hydrocortisone were found to consist of glutathione depletion and lowered glutathione reductase activities in alveolar epithelial type II cells, contrasted with unchanged act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…At the concentrations studied, zinc did not interfere with the assay. The analytical detection limit for glutathione was ≈0.2 nmol per mg of cellular protein [8]. GSSG was determined after GSH had reacted with 2-vinylpyridine (2 per 100 µl of acid cell extract at pH 7) for half an hour.…”
Section: Measurement Of Glutathione Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…At the concentrations studied, zinc did not interfere with the assay. The analytical detection limit for glutathione was ≈0.2 nmol per mg of cellular protein [8]. GSSG was determined after GSH had reacted with 2-vinylpyridine (2 per 100 µl of acid cell extract at pH 7) for half an hour.…”
Section: Measurement Of Glutathione Contentmentioning
confidence: 99%
“…Furthermore, toxicity is enhanced when cellular glutathione had been decreased. Additionally, pretreatment of alveolar epithelial cells with glucocorticoids is known to decrease cellular glutathione and such cells are more susceptible to zinc as compared to not pretreated cells [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, cellular glutathione was decreased in both alveolar epithelial cell lines, while content was increased in the fibroblast-like line (Walther, 2004). The cellular GR activity of all cell lines was decreased to about 10% or below this level after incubation of cells with toxic concentrations of zinc.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore zinc-mediated toxicity is explained by the glutathione depletion (Walther et al, 1999b) and HC is shown to affect the glutathione system by decreasing glutathione and glutathione reductase (GR) in alveolar epithelial cells (Walther, 2004). Therefore it seems probable that the increase ଝ Results of this investigation partly concern to the inaugural dissertation of R.S.…”
Section: Introductionmentioning
confidence: 96%